DEVELOPMENT OF E-HELP MANUAL USING GRAPHICAL USER INTERFACE (GUI) FOR BATTERY MANAGEMENT SYSTEM (BMS) IN ELECTRIC VEHICLE - Mohd Amin, N.H.; Ab Ghani, M.R.; Jidin, A.; Othman, S.; Jano, Z. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
GUI is commonly used in most applications. Each component in GUI activates itself to monitor, control and manage the system operation. This paper developed e-Help Manual module using Graphical User Interface (GUI) for Battery Management System (BMS) in Electric Vehicle (EV). Overcharge and over discharge often occur in the system without proper maintenance of the battery. Therefore, this study used GUI for BMS in EV to develop a user friendly electronic-Help (e-Help) manual with a few options; Let Me Do It auto (LMDI), Do It Yourself manual (DIY), and Others call for Technical Assistant (OTHERS) to reduce faults in the system, tasks in the battery troubleshooting and cost of battery maintenance. This study used hybrid (PI, PD, and LQR) controller in the system to control current and voltage flow of the external charger for the battery. As a result, the output performance was improved based on battery charging or discharging states of the Li-Ion characteristics in EV and the energy use was optimized.